Теорія і практика чисельно-польового визначення електромагнітних характеристик турбогенераторів при їх роботі в енергосистемі - Мілих, Володимир Іванович; Ревуженко, Світлана Афанасіївна (НТУ "ХПІ", 2019)
Представлено теоретичні основи та практичні аспекти визначення характеристик турбогенераторів, які пов'язують електромагнітні величини, властиві різним режимам їх роботи в енергосистемі. Це здійснюється найбільш адекватним способом – чисельно-польовим методом. Таким чином отримано низку характеристик потужного турбогенератора, а саме, характеристику неробочого ходу, характеристики повздовжнього та поперечного намагнічування від обмотки статора, характеристику короткого замикання, регулювальні й кутову характеристики та сім'ю U-подібних характеристик. Розрахунки виконано за допомогою автоматизованих чисельних розрахунків магнітних полів в програмному середовищі FEMM методом скінченних елементів із використанням створених скриптів Lua. Залежності штатних величин, які пов’язуються в стандартизованих характеристиках, супроводжуються додатково відповідними функціями електричних та кутових величин.

The theoretical bases and practical aspects of determining the characteristics of turbogenerators, which connect the electromagnetic quantities inherent in the different modes of their operation in the power system, are presented. This is carried out in the most appropriate form – by the numerical-field method. The calculation of the characteristics points is the solution of the inverse problem in which in most cases there are two basic and two variable values. This requires an iterative calculations. The assignment of the first approximations of the values of the variable quantities and the organization of the iterative characteristics calculation processes are shown. In this way, a number of characteristics of a powerful turbogenerator were obtained, namely, a characteristic of idling, characteristics of longitudinal and transverse magnetization from the stator winding, short-circuit characteristic, adjusting and angular characteristics, as well as a family of U-shaped characteristics. The calculations were performed using the automated numerical calculations of magnetic fields in the FEMM software environment by the finite element method, with the use of the created Lua scripts. Dependencies of standard values, which are connected in standardized characteristics, are additionally accompanied by corresponding functions of electrical and angular values. A number of pictures of magnetic fields corresponding to different specific points of characteristics are given.
Theory and practice of numerical-field determination of the electromagnetic characteristics of turbogenera-tors with their operation in the power system
Keywords: електромагнітні величини; магнітне поле; чисельні розрахунки; електрична машина; коротке замикання; номінальне навантаження; electromagnetic quantities; modes of operation; magnetic field; numerical calculations